Preparation method and application of microcrystalline graphite-based carbon-ceramic composite graphite

Through the composite process of high-purity microcrystalline graphite and polymethylsilane and other raw materials, a nanoscale silicon carbide second phase network is formed, which solves the performance problems of graphite materials in high temperature and irradiation environments, and achieves higher mechanical, thermal and oxidation resistance, extends service life and reduces production complexity and energy consumption.

CN119859062APending Publication Date: 2025-04-22HUNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510051336.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing graphite materials have problems such as high wear rate, poor impact resistance, easy oxidation and large irradiation deformation in high temperature and irradiation environments, which affect their application life and performance in nuclear reactors and other fields.

Method used

High-purity microcrystalline graphite is used to combine with raw materials such as polymethylsilane, toluene and divinylbenzene. Through direct mixing molding, heat treatment and two impregnation and calcining processes, a microcrystalline graphite/silicon carbide composite material is formed to form a nanoscale silicon carbide second phase network to improve the mechanical, thermal conductivity and oxidation resistance of graphite.

Benefits of technology

It significantly improves the density, interface strength, radiation resistance and performance uniformity of microcrystalline graphite-based carbon ceramic composite graphite, extends its service life, and reduces the complexity and energy consumption of the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859062A_ABST
    Figure CN119859062A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of microcrystalline graphite-based carbon-ceramic composite graphite, which comprises the following steps: directly mixing microcrystalline graphite powder and a polymethylsilane solution, molding, carrying out heat treatment to form a microcrystalline graphite / silicon carbide composite material, and carrying out twice impregnation and heat treatment on the microcrystalline graphite / silicon carbide composite material to improve the performance of the composite material. According to the invention, high-purity microcrystalline graphite is adopted, and the special microstructure of the microcrystalline graphite endows the microcrystalline graphite with a large number of communicated holes, so that silicon carbide can be filled into microcrystalline graphite particles to form a silicon carbide second-phase network, and the microcrystalline graphite / silicon carbide composite particles are obtained. The carbon-ceramic composite graphite prepared on the basis of the composite particles can improve the mechanical property, the heat-conducting property and the oxidation resistance of the graphite material, can more effectively inhibit the irradiation size change of the graphite on the nanoscale, and is a high-performance irradiation-resistant composite graphite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparation and application of carbon-ceramic composite graphite, and specifically to a preparation method and application of a novel microcrystalline graphite-based carbon-ceramic composite graphite prepared by compounding microcrystalline graphite with a liquid silicon carbide source. Background Art

[0002] Graphite materials have unique physical and chemical properties, excellent mechanical strength, good electrical and thermal conductivity, self-lubrication, high temperature resistance, neutron moderation performance and other advantages, and are widely used in nuclear engineering, chemical industry, food, machinery and aerospace. In addition, graphite also has disadvantages such as high wear rate, poor impact resistance and easy oxidation at high temperature, which leads to the decline of quality and durability of graphite parts. Therefore, while ensuring the excellent performance of graphite parts, it is particularly important to reduce the friction and wear of graphite parts and improve their anti-oxidation performance to improve the reliability and service life of graphite.

[0003] When graphite materials are used in advanced nuclear reactors such as high-temperature gas-cooled reactors or molten salt reactors, they work in a fast neutron irradiation environment, resulting in radiation damage, graphite crystal size changes, and changes in the volume of graphite materials, affecting the normal operation of the reactor. The radiation performance of nuclear graphite determines the life of the reactor. The mechanical properties and radiation resistance of silicon carbide are better than those of graphite, and the radiation deformation is small. By constructing a graphite / silicon carbide composite material, the radiation deformation of graphite can be limited by the silicon carbide second phase network, and the obtained carbon-ceramic composite graphite has excellent radiation resistance. At the same time, the carbon-ceramic composite material also has good wear resistance and oxidation resistance, and is suitable for replacing existing nuclear-grade graphite and isostatic graphite.

[0004] At present, the common methods for preparing silicified graphite are usually: chemical vapor deposition, chemical vapor reaction and liquid phase siliconization. Patent CN202410985892.9 reports a method for preparing silicified graphite using graphite powder and coke powder slurry as raw materials and then using liquid phase siliconization, which avoids the problem of low graphite content in the preparation process of silicified graphite. Patent CN201511017040.8 reports a method for preparing silicified graphite using a silicon carbide precursor through an impregnation-curing-cracking process, and obtains a high-density silicified graphite product. However, the number of impregnations is large, the preparation process is complicated, and it is impossible to avoid the problems of poor dispersion uniformity of the silicon carbide reinforcement phase in the graphite matrix and low interface bonding strength between graphite and silicon carbide. Summary of the invention

[0005] The present application provides a preparation method and application of microcrystalline graphite-based carbon ceramic composite graphite. The raw materials in the present application include high-purity microcrystalline graphite powder, polymethylsilane, toluene and divinylbenzene. The microcrystalline graphite powder, polymethylsilane solution and divinylbenzene are directly mixed and then formed, and a microcrystalline graphite / silicon carbide composite material is formed after heat treatment. The microcrystalline graphite / silicon carbide composite material is then impregnated and heat treated twice to improve the performance of the composite material. Microcrystalline graphite contains a large number of interconnected open pores with a pore size of less than 500nm. When microcrystalline graphite powder and polymethylsilane solution are directly compounded, the polymethylsilane solution can be immersed in the pores of graphite particles and coated on the surface of graphite particles. During the heat treatment process, polymethylsilane is pyrolyzed to generate silicon carbide, and a silicon carbide second phase network is formed inside and between graphite particles, thereby improving the mechanical properties, thermal conductivity and antioxidant properties of graphite. In particular, the silicon carbide second phase network formed inside the microcrystalline graphite particles plays a role in limiting the radiation deformation of graphite and stabilizing the radiation size change of the carbon-ceramic composite graphite material.

[0006] In order to achieve the above object, the present application provides a method for preparing microcrystalline graphite-based carbon-ceramic composite graphite, comprising the following steps:

[0007] Step S1: respectively obtaining high-purity microcrystalline graphite powder, toluene, polymethylsilane powder and divinylbenzene;

[0008] Step S2: preparing a polymethylsilane solution;

[0009] Step S3: mixing the polymethylsilane solution, divinylbenzene and high-purity microcrystalline graphite powder, kneading to obtain a paste, cooling, crushing and sieving to obtain a sieved material;

[0010] Step S4: isostatically pressing the sieved material, and then calcining it to 900° C.-1200° C. in a nitrogen atmosphere to obtain a primary calcined product;

[0011] Step S5: placing the primary calcined product into an impregnation tank and impregnating it under pressure to obtain a primary impregnation sample, wherein the impregnation solution is the polymethylsilane solution and divinylbenzene, and the polymethylsilane and divinylbenzene are configured at a mass ratio of 100:20. The primary impregnated product is calcined at 900°C-1200°C in a nitrogen atmosphere to obtain a secondary calcined product;

[0012] Step S6: Repeat the impregnation and calcination steps of S5 on the secondary calcined product to obtain microcrystalline graphite-based carbon-ceramic composite graphite.

[0013] Further, step S1 is as follows for preparing high-purity microcrystalline graphite: placing microcrystalline graphite with a fixed carbon content of ≥98% in an Acheson furnace for purification, heating the temperature to 1800-2000°C at a heating rate of 0.5-2°C / min in the first stage, introducing chlorine, and purifying for 0.5-2h, heating the temperature to 2000-2200°C in the second stage, introducing freon, and purifying for 1-5h, heating the temperature to 2600-2800°C in the third stage, keeping the temperature for 1-5h, and cooling with the furnace to obtain purified microcrystalline graphite; using a mechanical pulverizer to pulverize the purified microcrystalline graphite to obtain microcrystalline graphite particles, wherein the fixed carbon content of the microcrystalline graphite particles is greater than 99.995%, the porosity is ≥25%, and the particle size D 50 ≤20μm. Toluene is an organic compound with a chemical formula of C7H8. It is a colorless, volatile liquid with a special aromatic smell. Its molecular weight is 92 and its boiling point is about 110°C at normal pressure. The molecular weight of polymethylsilane is about 1300 and its softening point is 60°C. It has a high solubility in toluene. Pure polymethylsilane is a light yellow solid at room temperature and is flammable when exposed to air over a large area. Divinylbenzene (DVB) is an organic compound with a molecular formula of C 10 H 10 It also contains impurities such as diethylbenzene and ethylvinylbenzene. It is a light yellow transparent liquid with a molecular weight of 130 and a boiling point of about 190°C under normal pressure.

[0014] Furthermore, the specific method of mixing in step S2 is to slowly dissolve the polymethylsilane powder in a toluene solvent and stir and disperse it to obtain a light yellow solution with a mass fraction of 50-70%.

[0015] Furthermore, in step S3, the mass ratio of high-purity microcrystalline graphite to polymethylsilane is 80-85:15-20, the mass ratio of divinylbenzene to polymethylsilane is 70-90:10-30, the kneading equipment is a double planetary vacuum mixer, the kneading temperature is 80-100°C, the kneading time is about 30 minutes, and then the temperature is reduced to 60-70°C and vacuumed to remove the toluene solvent, the vacuum degree is about -0.1MPa, until the toluene is completely removed, and the material is cooled to room temperature, and then crushed and passed through a 100-150 mesh standard sieve.

[0016] Furthermore, the isostatic pressing process of step S4 is as follows: the secondary powder obtained in step S3 is loaded into a silicone rubber mold, and then placed in a cold isostatic press for molding. The pressurization rate during molding is about 200MPa / min, the maximum molding pressure is 150-200MPa, and the pressure is maintained for 5-10min to obtain a raw product; the raw product is heat treated in a roasting furnace, and in a nitrogen atmosphere, the temperature is increased to 120°C at a heating rate of 0.33°C / min, and then the temperature is increased to 600°C at a heating rate of 0.1°C / min, and then the temperature is increased to 900-1200°C at a heating rate of 1°C / min, and the temperature is maintained for 0.5-2h, and the product is taken out after cooling in the furnace to obtain a once-baked product.

[0017] Furthermore, the specific steps of impregnation in step S5 are as follows: the primary calcined product is placed in an impregnation tank containing polymethylsilane solution and divinylbenzene, the polymethylsilane and divinylbenzene are configured in a mass ratio of 100:20, and the pressure is increased to 1-3MPa and maintained for 0.5-2h to obtain a primary impregnated product.

[0018] Furthermore, the calcination and impregnation process in step S6 is the same as the above-mentioned S5 process, and the number of calcination and impregnation is 3 times and 2 times respectively, to obtain a novel microcrystalline graphite-based carbon-ceramic composite graphite.

[0019] The present invention provides a novel microcrystalline graphite-based carbon-ceramic composite graphite, which is prepared by the above raw materials and process. The novel microcrystalline graphite-based carbon-ceramic composite graphite has a density of 1.95-2.20 g / cm3, a flexural strength of 50-60 MPa, a compressive strength of 110-120 MPa, an open porosity of ≤5%, a thermal conductivity of ≥100 W / (M·K), and a thermal expansion coefficient of ≤5×10 -6 / K.

[0020] The technical solution provided by this application has at least the following beneficial effects compared with the prior art:

[0021] 1) This application realizes a unique carbon-ceramic composite graphite structure design. High-purity microcrystalline graphite is used. The special microstructure of microcrystalline graphite gives it a large number of interconnected open pores, which can allow silicon carbide to fill into the microcrystalline graphite particles, forming a nanoscale silicon carbide second phase network, and obtaining microcrystalline graphite / silicon carbide composite particles, which more effectively suppress the irradiation size change of graphite at the nanoscale. The existing technology uses coke as an aggregate, and the silicon source cannot enter the interior of the particles, and cannot form a nanoscale carbon-ceramic composite structure.

[0022] 2) This application obtains a new type of microcrystalline graphite-based carbon-ceramic composite nuclear-grade graphite, with a graphite and silicon carbide second phase network nanoscale composite structure inside the aggregate, and a silicon carbide reinforcement phase between the aggregates, achieving uniform dispersion of the reinforcement phase in the graphite matrix. The silicon carbide second phase generated by in-situ cracking inside and outside the aggregate improves the product's density, interface strength, fast neutron irradiation performance and performance uniformity of the graphite composite material.

[0023] 3) The preparation method of the present application is simple, with fewer impregnation and roasting times, a relatively short overall production cycle, and a low heat treatment temperature (900-1200°C), and does not require high energy consumption processes such as traditional silicified graphite liquid phase infiltration-reaction sintering. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1The transmission electron micrographs after focused ion beam masking are shown in FIG. 1 , wherein (a) is a micrograph of the product of Example 2, and (b) is a micrograph of the product of Comparative Example 1. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to understand the present application more clearly, the present application is further described in detail below in conjunction with examples and drawings. However, it should be understood that the following examples are only preferred implementation methods of the present application, and the scope of protection required by the present application shall be based on the scope defined in the claims.

[0026] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0027] Example 1

[0028] A method for preparing microcrystalline graphite-based carbon-ceramic composite graphite comprises the following steps:

[0029] Step S1: Preparation of high-purity microcrystalline graphite powder: Microcrystalline graphite with a fixed carbon content of ≥98% is placed in an Acheson furnace for purification. In the first stage, the temperature is raised to 2000°C at a heating rate of 1°C / min, and freon is introduced for purification for 2h. In the second stage, the temperature is raised to 2200°C, chlorine is introduced, and purification is performed for 3h. In the third stage, the temperature is raised to 2800°C, and the temperature is kept for 2h. The purified microcrystalline graphite powder is obtained by cooling with the furnace. The fixed carbon content of the microcrystalline graphite particle powder is greater than 99.995%, the porosity is 25-30%, and the particle size D 50 =20μm;

[0030] Step S2: preparing a polymethylsilane solution with a mass fraction of 60% by weight using toluene as solvent;

[0031] Step S3: high-purity microcrystalline graphite powder and polymethylsilane solution are kneaded, wherein the mass ratio of high-purity microcrystalline graphite powder to polymethylsilane is 85:15, the kneading equipment is a double planetary mixer, the kneading temperature is 90°C, the kneading time is about 30 minutes, and then the temperature is reduced to 70°C and vacuumed to remove the toluene solvent, the vacuum degree is -0.1MPa, until the toluene is completely removed, and the material is cooled to room temperature, and then crushed and passed through a 100-mesh standard sieve to obtain a sieved material;

[0032] Step S4: loading the screened material into a silicone rubber mold, and then placing it in a cold isostatic press for molding, with a pressurization rate of 200 MPa / min and a maximum molding pressure of 150 MPa, and maintaining the pressure for 5 min to obtain a raw product; heat-treating the raw product in a roasting furnace, heating it to 120°C at a heating rate of 0.33°C / min under a nitrogen atmosphere, then heating it to 600°C at a heating rate of 0.1°C / min, and then heating it to 1000°C at a heating rate of 1°C / min, maintaining the temperature for 1 h, and taking it out after cooling to obtain a primary roasted product;

[0033] Step S5: placing the primary calcined product into an impregnation tank filled with polymethylsilane solution, wherein polymethylsilane and divinylbenzene are configured in a mass ratio of 100:20, pressurizing to 3 MPa and maintaining the pressure for 2 hours to obtain a primary impregnation sample; calcining the primary impregnation product to 1000° C. to obtain a secondary calcined product.

[0034] Step S6: Repeat the impregnation and calcination steps of S5 on the secondary calcined product to obtain microcrystalline graphite-based carbon-ceramic composite graphite.

[0035] The density of microcrystalline graphite-based carbon-ceramic composite graphite is 1.99g / cm 3 , flexural strength is 52MPa, compressive strength is 113.2MPa, open porosity is 4.7%, thermal conductivity is 103.2W / (M·K), thermal expansion coefficient is 4.3*10 -6 / K.

[0036] Example 2

[0037] This embodiment is basically the same as Embodiment 1, and the only difference is the difference in the mass ratio of high-purity microcrystalline graphite powder to polymethylsilane.

[0038] Step S1: Preparation of high-purity microcrystalline graphite powder: Microcrystalline graphite with a fixed carbon content of ≥98% is placed in an Acheson furnace for purification. In the first stage, the temperature is raised to 2000°C at a heating rate of 1°C / min, and freon is introduced for purification for 2h. In the second stage, the temperature is raised to 2200°C, chlorine is introduced, and purification is performed for 3h. In the third stage, the temperature is raised to 2800°C, and the temperature is kept for 2h. The purified microcrystalline graphite powder is obtained by cooling with the furnace. The fixed carbon content of the microcrystalline graphite particle powder is greater than 99.995%, the porosity is 25-30%, and the particle size D 50 =20μm;

[0039] Step S2: preparing a polymethylsilane solution with a mass fraction of 60% by weight using toluene as solvent;

[0040] Step S3: high-purity microcrystalline graphite powder and polymethylsilane solution are kneaded, wherein the mass ratio of high-purity microcrystalline graphite powder to polymethylsilane is 80:20, the kneading equipment is a double planetary mixer, the kneading temperature is 90°C, the kneading time is about 30 minutes, and then the temperature is reduced to 70°C and vacuumed to remove the toluene solvent, the vacuum degree is -0.1MPa, until the toluene is completely removed, and the material is cooled to room temperature, and then crushed and passed through a 100-mesh standard sieve to obtain a sieved material;

[0041] Step S4: loading the screened material into a silicone rubber mold, and then placing it in a cold isostatic press for molding, with a pressurization rate of 200 MPa / min and a maximum molding pressure of 150 MPa, and maintaining the pressure for 5 min to obtain a raw product; heat-treating the raw product in a roasting furnace, heating it to 120°C at a heating rate of 0.33°C / min under a nitrogen atmosphere, then heating it to 600°C at a heating rate of 0.1°C / min, and then heating it to 1000°C at a heating rate of 1°C / min, maintaining the temperature for 1 hour, and taking it out after cooling to obtain a primary roasted product;

[0042] Step S5: placing the primary calcined product into an impregnation tank filled with polymethylsilane solution, wherein polymethylsilane and divinylbenzene are configured in a mass ratio of 100:20, pressurizing to 3 MPa and maintaining the pressure for 2 hours to obtain a primary impregnation sample; calcining the primary impregnation product to 1000° C. to obtain a secondary calcined product.

[0043] Step S6: Repeat the impregnation and calcination steps of S5 on the secondary calcined product to obtain microcrystalline graphite-based carbon-ceramic composite graphite.

[0044] The density of microcrystalline graphite-based carbon-ceramic composite graphite is 2.07g / cm 3 , flexural strength 56MPa, compressive strength 115.6MPa, open porosity 4.1%, thermal conductivity 109.4W / (M·K), thermal expansion coefficient 4.1*10 -6 / K.

[0045] Example 3

[0046] This embodiment is basically the same as embodiment 2, except that 10% of divinylbenzene (DVB) is added in step 3 as a crosslinking agent for polymethylsilane (the crosslinking reaction between divinylbenzene and polymethylsilane can improve the density of the silicon carbide phase produced by pyrolysis).

[0047] Step S1: Preparation of high-purity microcrystalline graphite powder: Microcrystalline graphite with a fixed carbon content of ≥98% is placed in an Acheson furnace for purification. In the first stage, the temperature is raised to 2000°C at a heating rate of 1°C / min, and freon is introduced for purification for 2h. In the second stage, the temperature is raised to 2200°C, chlorine is introduced, and purification is performed for 3h. In the third stage, the temperature is raised to 2800°C, and the temperature is kept for 2h. The purified microcrystalline graphite powder is obtained by cooling with the furnace. The fixed carbon content of the microcrystalline graphite particle powder is greater than 99.995%, the porosity is 25-30%, and the particle size D 50 =20μm;

[0048] Step S2: preparing a polymethylsilane solution with a mass fraction of 60% by weight using toluene as solvent;

[0049] Step S3: high-purity microcrystalline graphite powder, polymethylsilane solution and divinylbenzene are kneaded, wherein the mass ratio of high-purity microcrystalline graphite powder, polymethylsilane and divinylbenzene is about 79:19:2, the kneading equipment is a double planetary mixer, the kneading temperature is 90°C, the kneading time is about 30 minutes, and then the temperature is reduced to 70°C and vacuumed to remove the toluene solvent, the vacuum degree is -0.1MPa, until the toluene is completely removed, and the material is cooled to room temperature, and then sieved through a 100-mesh standard sieve to obtain a sieved material;

[0050] Step S4: loading the screened material into a silicone rubber mold, and then placing it in a cold isostatic press for molding, with a pressurization rate of 200 MPa / min and a maximum molding pressure of 150 MPa, and maintaining the pressure for 5 min to obtain a raw product; heat-treating the raw product in a roasting furnace, heating it to 120°C at a heating rate of 0.33°C / min under a nitrogen atmosphere, then heating it to 600°C at a heating rate of 0.1°C / min, and then heating it to 1000°C at a heating rate of 1°C / min, maintaining the temperature for 1 h, and taking it out after cooling to obtain a primary roasted product;

[0051] Step S5: placing the primary calcined product into an impregnation tank filled with polymethylsilane solution, wherein polymethylsilane and divinylbenzene are configured in a mass ratio of 100:20, pressurizing to 3 MPa and maintaining the pressure for 2 hours to obtain a primary impregnation sample; calcining the primary impregnation product to 1000° C. to obtain a secondary calcined product.

[0052] Step S6: Repeat the impregnation and calcination steps of S5 on the secondary calcined product to obtain microcrystalline graphite-based carbon-ceramic composite graphite.

[0053] The density of microcrystalline graphite-based carbon-ceramic composite graphite is 2.19g / cm 3 , flexural strength 58.7MPa, compressive strength 123.5MPa, open porosity 3.5%, thermal conductivity 114.5W / (M·K), thermal expansion coefficient 3.8*10 -6 / K.

[0054] Comparative Example 1

[0055] In this comparative example, microcrystalline graphite powder is used as aggregate, microcrystalline graphite-based isostatically pressed graphite is prepared by a conventional preparation method, and then impregnated with a polymethylsilane solution to obtain a graphite / SiC composite material. The specific method is as follows:

[0056] Step S1: The high-purity microcrystalline graphite powder raw material described in the above embodiment is used, and the final density is 1.69 g / cm2 after kneading (high-purity microcrystalline graphite powder and molten coal tar are kneaded in a kneader at 180°C for 2 hours) - molding (150 MPa cold isostatic pressing for 5 minutes) - roasting (heating to 1000°C for heat treatment and insulation for 1 hour) - impregnation (impregnation with molten asphalt under 3 MPa pressure) - graphitization (heating to 2800°C for heat treatment and insulation for 30 minutes) and other processes. 3 Finished graphite.

[0057] Step S2: placing the graphite blank into an impregnation tank filled with polymethylsilane solution, wherein the polymethylsilane and divinylbenzene are configured in a mass ratio of 100:20, pressurizing to 3 MPa and maintaining the pressure for 2 hours to obtain an impregnated sample; discharging the material, and taking out the graphite blank containing the impregnation solution.

[0058] Step S3: heat-treating the graphite body containing the impregnation liquid in a nitrogen atmosphere, heating the body to 120°C at a heating rate of 0.33°C min-1, then heating the body to 600°C at a heating rate of 0.1°C min-1, and finally heating the body to 1000°C at a heating rate of 1°C / min-1, keeping the temperature for 1 hour, cooling the body, and taking the body out to obtain a primary calcined product;

[0059] Step S4: Repeat the impregnation-calcination process in step 2 and step 3 for the once-calcined product to obtain a graphite / silicon carbide composite material that has been impregnated and calcined twice.

[0060] The performance is as follows: density 1.90g / cm 3 , flexural strength 45.3MPa, compressive strength 98MPa, open porosity 4.7%, thermal conductivity 91.7W / (M·K), thermal expansion coefficient 4.3*10-6 / K.

[0061] In order to prove that the present invention can form a silicon carbide phase filling inside the microcrystalline graphite and can effectively inhibit the irradiation size change of graphite at the nanoscale, the focused ion beam and transmission electron microscopy technology were used to observe the embodiment 2 ( Figure 1 a) and Comparative Example 1 ( Figure 1The microstructure of the sample b) in b is characterized. The microcrystalline graphite in b has typical grid-like pores (the pores are shown as white holes in b), and the pores of the microcrystalline graphite in a are filled. Elemental analysis shows that it has a silicon carbide phase. Existing studies have shown that silicon carbide has better radiation resistance than graphite. Therefore, the present invention can improve the radiation resistance of microcrystalline graphite at the nanoscale.

[0062] Table 1 Technical solutions of various embodiments and comparative examples and performance of the obtained products

[0063]

Claims

1. A method for preparing microcrystalline graphite-based carbon-ceramic composite graphite, comprising the following steps: Step S1: respectively obtaining high-purity microcrystalline graphite powder, toluene, polymethylsilane powder and divinylbenzene; Step S2: preparing a polymethylsilane solution; Step S3: mixing the polymethylsilane solution, divinylbenzene and high-purity microcrystalline graphite powder, kneading to obtain a paste, and then cooling and crushing and sieving to obtain a sieved material; Step S4: isostatically pressing the sieved material, and then calcining it to 900° C.-1200° C. in a nitrogen atmosphere to obtain a primary calcined product; Step S5: placing the primary calcined product into an impregnation tank and impregnating it under pressure to obtain a primary impregnation sample, wherein the impregnation solution is the polymethylsilane solution and divinylbenzene, and the polymethylsilane and divinylbenzene are configured at a mass ratio of 100:

20. The primary impregnated product is calcined at 900°C-1200°C in a nitrogen atmosphere to obtain a secondary calcined product; Step S6: Repeat the impregnation and calcination steps of S5 on the secondary calcined product to obtain microcrystalline graphite-based carbon-ceramic composite graphite.

2. The method for preparing microcrystalline graphite-based carbon-ceramic composite graphite according to claim 1, characterized in that: The preparation steps of the high-purity microcrystalline graphite are as follows: placing microcrystalline graphite with a fixed carbon content of ≥98% in an Acheson furnace for purification, heating the temperature to 1800-2000°C at a heating rate of 0.5-2°C / min in the first stage, introducing chlorine gas, and purifying for 0.5-2h, heating the temperature to 2000-2200°C in the second stage, introducing Freon, and purifying for 1-5h, and heating the temperature to 2600-2800°C in the third stage, keeping the temperature for 1-5h, and cooling with the furnace to obtain purified microcrystalline graphite; using a mechanical pulverizer to pulverize the purified microcrystalline graphite to obtain high-purity microcrystalline graphite powder, wherein the high-purity microcrystalline graphite powder has a fixed carbon content of greater than 99.995%, a porosity of ≥25%, and a particle size D 50 ≤20μm.

3. The method for preparing microcrystalline graphite-based carbon-ceramic composite graphite according to claim 1, characterized in that: The preparation method of the polymethylsilane solution in step S2 is: slowly dissolving the polymethylsilane powder in a toluene solvent and stirring and dispersing the mixture to obtain a light yellow solution with a mass fraction of 50-70%.

4. The method for preparing microcrystalline graphite-based carbon-ceramic composite graphite according to claim 1, characterized in that: In step S3, the mass ratio of high-purity microcrystalline graphite powder to polymethylsilane is 80-85:15-20, and the mass ratio of divinylbenzene to polymethylsilane is 70-90:10-30. The kneading equipment is a double planetary vacuum mixer, the kneading temperature is 80-100°C, the kneading time is about 30 minutes, and then the temperature is lowered to 60-70°C to evacuate the toluene solvent, the vacuum degree is -0.1MPa, until the toluene is completely removed, and the material is cooled to room temperature, taken out, crushed and passed through a 100-150 mesh standard sieve.

5. The method for preparing microcrystalline graphite-based carbon-ceramic composite graphite according to claim 1, characterized in that: The isostatic pressing process in step S4 is as follows: the sieved material is loaded into a silicone rubber mold, and then placed in a cold isostatic press for molding. The pressurization rate during molding is 200MPa / min, the maximum molding pressure is 150-200MPa, and the pressure is maintained for 5-10min to obtain a raw product; the raw product is heat treated in a roasting furnace, and in a nitrogen atmosphere, the temperature is increased to 120°C at a heating rate of 0.33°C / min, and then the temperature is increased to 600°C at a heating rate of 0.1°C / min, and then the temperature is increased to 900-1200°C at a heating rate of 1°C / min, and the temperature is maintained for 0.5-2h, and the raw product is cooled with the furnace to obtain a primary roasted product.

6. The method for preparing microcrystalline graphite-based carbon-ceramic composite graphite according to claim 1, characterized in that: The specific steps of impregnation in step S5 are as follows: the primary calcined product is placed in an impregnation tank filled with polymethylsilane solution and divinylbenzene, the polymethylsilane and divinylbenzene are configured in a mass ratio of 100:20, and the pressure is increased to 1-3MPa and maintained for 0.5-2h to obtain the primary impregnated product.

7. The method for preparing microcrystalline graphite-based carbon-ceramic composite graphite according to claim 1, characterized in that: In step S6, the number of calcination and impregnation is 3 times and 2 times respectively.

8. A use of microcrystalline graphite-based carbon-ceramic composite graphite, characterized in that: The method for preparing the microcrystalline graphite-based carbon-ceramic composite graphite is as described in any one of claims 1 to 7, and the microcrystalline graphite-based carbon-ceramic composite graphite can be used to replace existing nuclear-grade graphite or isostatic graphite.

Citation Information

Patent Citations

  • Preparation method of graphite / SiC composite material

    CN105481477A

  • Silicified graphite and preparation method thereof

    CN118851766A